IBADAT, THE BODY AND IDENTITY: ISLAMIC RITUALS AND THE CONSTRUCTION OF MUSLIM IDENTITY - Hidayat, Medhy Aginta (Department of Social Science, Faculty of Social Science &Law, Universitas Negeri Surabaya, 2017)
This library-based theoretical paper examines three types of Islamic rituals or ibadat, that is salat, sawm, and hajj, to understand the important of embodied rituals in the construction of Muslim identity. By utilizing several key theoretical ideas including Durkheim?s Sacred and Profane, Bell?s ritual and ritualization, and Whitehouse?s modes of religiosity, this paper corroborates the previous findings in the religious and sociological studies that the body plays an important role in the construction of identity, including religious identity such as Muslim identity. This embodied or ritualized body, with its characteristics of formality, fixity, and repetition, constructs, upholds, enforces and maintains Muslim identity through its rituals of salat, sawm, and hajj